Psychological testing of individuals in stressful situations: test-taking attitudes and perception of visual stimuli - B. V. Biron; I. A. Bulakh; O. O. Volkova; D. F. Olkhovskyi; V. S. Rodin (Journal of Ophthalmology, 2022)
Background: Professional activities of individuals under stressful conditions affect their psychic processes and capability to work. The social-cognitive distortions developing under these conditions require a comprehensive assessment involving, particularly, quantitative assessment. The relevant psychometric instruments for detecting these distortions should be carefully psychometrically adapted.